1992
DOI: 10.1080/10511482.1992.9521117
|View full text |Cite
|
Sign up to set email alerts
|

Retreat from homeownership: A comparison of the generations and the states

Abstract: Homeownership is a topic of widespread policy concern, and the 1990 census provides a unique opportunity to review trends of the 1980s for subareas of the nation and subgroups of the population. This paper addresses three main questions. First, in which states did the overall level of homeownership fare best during the 1980s, and in which did the level decline most? Second, did the level of homeownership fall where house values rose most steeply? Finally, in which states did the large baby-boom generation fare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 2 publications
(1 reference statement)
2
8
0
Order By: Relevance
“…Local market conditions, such as house prices and affordability, have been identified as factors that may encourage or hinder homeownership. Each of these areas and its relation with homeownership has been examined in depth in several studies (Beamish, 1994;Goss, 1994;Ha & Weber, 1994;Hughes, 1991;Hughes, 1996;Johnson, 1989;McCray, 1994;Myers, Peiser, & Schwann, 1994;Weber, 1994) for all the states as well as for specific regions in rural and urban communities. These studies have found that homeownership has been positively or negatively correlated with such factors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Local market conditions, such as house prices and affordability, have been identified as factors that may encourage or hinder homeownership. Each of these areas and its relation with homeownership has been examined in depth in several studies (Beamish, 1994;Goss, 1994;Ha & Weber, 1994;Hughes, 1991;Hughes, 1996;Johnson, 1989;McCray, 1994;Myers, Peiser, & Schwann, 1994;Weber, 1994) for all the states as well as for specific regions in rural and urban communities. These studies have found that homeownership has been positively or negatively correlated with such factors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For those between 30 and 34, the rate fell from 57.1 % to 53.2% during the decade (Callis, 1990;Joint Center for Housing Studies 1994. Homeownership rates stabilized and inched up slightly in the 199Os, but the American dream is still beyond the reach of many young families, not only those who live in areas with rising home prices, but also those living in areas where housing prices (along with income and employment) are declining (Joint Center for Housing Studies, 1994Studies, , 1995Myers, Peiser, Schwann, & Pitkin, 1992). A census bureau study found that in 1991 91.2% of renter households (including 86.7% of married couples) could not afford to buy the median price house in the region where they live (Fronczek & Savage, 1993).…”
Section: Declining Homeownershipmentioning
confidence: 99%
“…Homeownership has long been considered the centerpiece of the American dream, a notion confirmed by Fannie Maecommissioned surveys conducted by Hart-Teeter Research (Fannie Mae 1992). It has also been regarded as a measure of the American standard of living-a barometer of economic and residential well-being (Myers et al 1992). Homeownership has been described as binding together a diverse America (Sternlieb and Hughes 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Homeownership is considered important for other reasons as well (Eggers and Burke 1995;Myers et al 1992). For households, it can promote savings and serve as an investment vehicle; provide a psychological sense of stability, well-being, satisfaction, and achievement; and yield a higher quality residential environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation